If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 2000 = 17 + 2x Reorder the terms: 2000 + 15x = 17 + 2x Solving 2000 + 15x = 17 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2000 + 15x + -2x = 17 + 2x + -2x Combine like terms: 15x + -2x = 13x 2000 + 13x = 17 + 2x + -2x Combine like terms: 2x + -2x = 0 2000 + 13x = 17 + 0 2000 + 13x = 17 Add '-2000' to each side of the equation. 2000 + -2000 + 13x = 17 + -2000 Combine like terms: 2000 + -2000 = 0 0 + 13x = 17 + -2000 13x = 17 + -2000 Combine like terms: 17 + -2000 = -1983 13x = -1983 Divide each side by '13'. x = -152.5384615 Simplifying x = -152.5384615
| 3*(x+2)-8=4*(x-2)+3x | | 15+2000=17-1x | | (7x^3-by^4)(7x^3-6y^4)-(7x^3-6y^4)= | | 4+3x=8*(x+3)+1 | | 3/4(12x-10)= | | (n+1)*2=14 | | 4,+3=13-m | | (4/3y)+(5/2y)=1 | | 7*(x-8)=-2x+1 | | 15+2000=-17-2x | | 7*(x-8)=-2x+2 | | -(-8k-6)=1-(3-6k) | | 2(x+2)+3(x-1)=8 | | 23-x=3 | | 3y-9+y+23=6+6y+14-4y | | 15-2000=17-2x | | 4x-5=7*(x-10) | | 24/6a | | 5(5+c)=4(c-3) | | -3x-2(-6+6x)=(x+2) | | 2+5*(x+2)=7x+1 | | y-25=-7 | | 6x+4=3+19 | | 19-(x+8)=8x-7 | | 15-2000=17+2x | | 3(5y+2)-5=2(y-3) | | x+6x+11=39+3x | | 18+6(z-3)=5z | | 6(7-7x)+6(x+7)=12 | | 15+2000=17+2x | | 6p^2-11pj-10j^2=0 | | 2p+2=-18 |